Rhinovirus C Is Associated With Severe Wheezing and Febrile Respiratory Illness in Young Children. Issue 4 (April 2020) - Erkkola, Riku; Turunen, Riitta; Räisänen, Kati; Waris, Matti; Vuorinen, Tytti; Laine, Miia; Tähtinen, Paula; Gern, James E.; Bochkov, Yury A.; Ruohola, Aino; Jartti, Tuomas
Abstract : Background: Rhinovirus is the most common virus causing respiratory tract illnesses in children. Rhinoviruses are classified into species A, B and C. We examined the associations between different rhinovirus species and respiratory illness severity. Methods: This is a retrospective observational cohort study on confirmed rhinovirus infections in 134 children 3–23 months of age, who were enrolled in 2 prospective studies on bronchiolitis and acute otitis media, respectively, conducted simultaneously in Turku University Hospital, Turku, Finland, between September 2007 and December 2008. Results: Rhinovirus C is the most prevalent species in our study, and it was associated with severe wheezing and febrile illness. We also noted that history of atopic eczema was associated with wheezing. Conclusions: Our understanding of rhinovirus C as the most pathogenic rhinovirus species was fortified. Existing research supports the idea that atopic characteristics are associated with the severity of the rhinovirus C-induced illness. Abstract : Supplemental Digital Content is available in the text.